ASSESSMENT OF PRESCRIBING PATTERN AMONG ORTHOPEDIC IN-PATIENTS USING WHO PRESCRIBING INDICATORS - S, Abhilash; Rao, Rashmi R; Yadunath P, Sivaguha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Evaluating the prescribing indicators regularly help to monitor the prescriptions to reduce indiscriminate use of drugs. The present study was conducted to explore the prescribing pattern in orthopedic in-patients using the WHO prescribing indicators in a tertiary care teaching hospital, Mangalore. Methods: Data was collected from case records of orthopedic in-patients regarding patient demographics, diagnosis, and details of drugs in a structured pro forma and analyzed for the WHO prescribing indicators using descriptive statistics. Values are expressed as mean Â± standard deviation, percentages as applicable. Results: A total of 379 patient prescriptions were included in the study which consisted of 2195 drugs. Of the 379 patients, 221 (58.3%) were male and 158 (41.7%) were female. The mean age group of the patients was 44 years. Acute trauma such as fractures, tendon damage, and disc prolapse (57.8%) were the most common indications for admission. Analgesics were the most commonly prescribed group of drugs comprising 27.28% of the prescriptions followed by multivitamins (20.68%) and proton-pump inhibitors (17.12%). The most commonly prescribed analgesic was nonsteroidal anti-inflammatory drugs (86.81%). Most of the drugs (65.80%) were administered through the oral route and 40.31% of drugs were fixed-dose combinations. The mean number of drugs per prescription was 5.79Â± 2.59. Antibiotics were prescribed in 60.4% of the prescriptions. 76.3% of prescriptions were with injectables. Use of drugs by generic name was 7.7% and only 44% of drugs were from the national list of essential medicines 2015. Conclusion: The study provides an insight into the prescribing pattern in orthopedic in-patients. It highlights the importance of emphasizing rational drug prescribing and toward improving awareness of the physicians and medical students to the WHO recommended standards on prescribing indicators.